A theoretical study on the formation and oxidation mechanism of hydroxyalkylsulfonate in the atmospheric aqueous phase. Issue 47 (30th August 2019) - Zhang, Danna; Lv, Guochun; Sun, Xiaomin; Zhang, Chenxi; Li, Zhiqiang
Abstract : We report the formation of an important organosulfur compound HMS and its oxidation using theoretical calculation. Abstract : Hydroxymethanesulfonate (HMS) is an important organosulfur compound in the atmosphere. In this work, we studied the formation mechanism of HMS via the reaction of formaldehyde with dissolved SO2 using the quantum chemistry calculations. The results show that the barrier (9.7 kcal mol −1 ) of the HCHO + HSO3 − reaction is higher than that (1.6 kcal mol −1 ) of the HCHO + SO3 2− reaction, indicating that the HCHO + SO3 2− reaction is easier to occur. For comparison, the reaction of acetaldehyde with dissolved SO2 also was discussed. The barriers for the CH3 CHO + HSO3 − reaction and CH3 CHO + SO3 2− reaction are 16.6 kcal mol −1, 2.5 kcal mol −1, respectively. This result suggests that the reactivity of HCHO with dissolved SO2 is higher than that of CH3 CHO. The further oxidation of CH2 (OH)SO3 − and CH3 CH(OH)SO3 − by an OH radical and O2 shows that the SO5 ˙ − radical can be produced.